The Influence of Financial Literacy, Financial Inclusion and Consumptive Behavior on Student Interests in Management Department, Faculty of Economics and Business, Labuhanbatu University in Using Financial Institution Products and Services - Mulkan Ritonga; Furi Windari; Tiurlina Hasmawati Sihite; Muhammad Ali Al Ihsan; Marlina Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
In increasing the interest of students to be involved in using the products and services of financial institutions, of course, students must have adequate financial knowledge or literacy, besides that students must also have easy and broad access to financial institution products and services (financial inclusion). Students' interest in using the products and services of financial institutions will be in line with their consumptive behavior in everyday life. This study aims to determine the effect of financial literacy, financial inclusion and consumptive behavior on student interest in using financial institution products and services. This research was conducted on students majoring in management, faculty of economics and business, Labuhanbatu University, totaling 133 people as a sample determined by simple random sampling technique. Testing of research primary data was conducted using IBM SPSS software version 20. To determine the effect between variables, a hypothesis test was carried out which first tested the classical assumption as a prerequisite for statistical analysis. The results showed that financial literacy partially had a positive and significant effect on student interest with a significance of 0.012 <0.05. Financial inclusion partially has a positive and significant effect on student interest with a significance value of 0.000 <0.05, consumptive behavior partially has a positive and significant effect on student interest. While simultaneously financial literacy, financial inclusion and consumptive behavior have a positive and significant effect on student interest with a significance value of 0.000 <0.05, with a contribution of 0.881 or 88.10% influence, while the rest is influenced by other factors not examined in this study.